A Survey of Material Actuation Enhancement Approaches for Adaptive Architecture - Huang, Sheng-Yang (ITB Journal Publisher, DRPM ITB, 2024)
This study examined design approaches for enhancing material actuation in adaptive architecture, aiming to make it perceptible for human cognitive engagement. Over recent decades, material actuation has gained attention as a sustainable alternative to mechanical actuation in architectural adaptation, utilizing materials’ intrinsic properties. This shift mitigates environmental concerns and enhances material engagement in spatial cognition. Enhancing material actuation’s effectiveness involves addressing inherent material limitations to ensure perceptibility in architectural work. This study explored new-structuralist adaptive design cases, categorizing enhancement approaches into ‘thinning’, ‘folding’, ‘aggregation’, ‘layering’, and ‘composite’. These strategies are pivotal in both pre-actuation and in-actuation phases of design and fabrication, facilitating interaction between humans and materials. The research methodology involved sourcing post-2010 publications from Google Scholar using keywords related to new materiality and architectural design. Selected articles featuring ‘material actuation’ were analyzed for their methodologies. Through clustering, five primary enhancement strategies were identified. This paper evaluates each approach’s benefits and limitations, highlighting potential utility concerns in material-based architectural adaptations. The analysis offers insight into material actuation’s role in adaptive architecture, emphasizing its environmental and cognitive implications.